2017
DOI: 10.1002/marc.201600723
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Mechanical Properties of Electrospun Nanofiber Mats through Controllable Welding at the Cross Points

Abstract: This communication describes a simple and effective method for welding electrospun nanofibers at the cross points to enhance the mechanical properties of their nonwoven mats. The welding is achieved by placing a nonwoven mat of the nanofibers in a capped vial with the vapor of a proper solvent. For polycaprolactone (PCL) nanofibers, the solvent is dichloromethane (DCM). The welding can be managed in a controllable fashion by simply varying the partial pressure of DCM and/or the exposure time. Relative to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
76
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 29 publications
(34 reference statements)
3
76
0
1
Order By: Relevance
“…When 70% ethanol solution was used to generate the vapor, the nanofibers were welded at their cross points even just after 1 and 3 min of exposure, but there were no significant changes to the morphology and geometric structure of the nanofibers away from the cross points ( Figure 3D,E). [20] As for the PLGA nanofibers, the segments away from the cross points still exhibited a fibrous morphology, indicating that the welding of PLGA nanofibers was mainly induced by the swelling of ethanol molecules. When pure ethanol was used to generate the vapor, the welding at cross points was further enhanced when compared with the case involving the vapor from 70% ethanol solution and for 1 min of exposure ( Figure 3G).…”
Section: Doi: 101002/marc201900579mentioning
confidence: 93%
See 1 more Smart Citation
“…When 70% ethanol solution was used to generate the vapor, the nanofibers were welded at their cross points even just after 1 and 3 min of exposure, but there were no significant changes to the morphology and geometric structure of the nanofibers away from the cross points ( Figure 3D,E). [20] As for the PLGA nanofibers, the segments away from the cross points still exhibited a fibrous morphology, indicating that the welding of PLGA nanofibers was mainly induced by the swelling of ethanol molecules. When pure ethanol was used to generate the vapor, the welding at cross points was further enhanced when compared with the case involving the vapor from 70% ethanol solution and for 1 min of exposure ( Figure 3G).…”
Section: Doi: 101002/marc201900579mentioning
confidence: 93%
“…[12][13][14] In our prior studies, we have demonstrated the fabrication of scaffolds with both uniaxially aligned and random nanofibers in adjacent regions to recapitulate the structural organization of collagen fibrils at the tendon-to-bone insertion. [20] Because of swelling, the nanofibers could be welded at their cross points and even over-welded (i.e., swollen and fused together to form a dense film) by increasing the partial pressure of DCM vapor and/or the exposure time. [18,19] It was reported that the electrospun nanofibers in a nonwoven mat could be welded at their cross points when the sample was exposed to the vapor from a solvent.…”
Section: Doi: 101002/marc201900579mentioning
confidence: 99%
“…[1][2][3][4][5] Ty pically,t he electrospun nanofibers are collected as nonwoven mats in al ayer-bylayer fashion, resulting in weak interaction between the nanofibers.Upon stretching,the mat will be easily deformed as ar esult of slipping between the nanofibers.A ne ffective way for enhancing the mechanical strength of the mat is to weld the nanofibers at their cross points.T ypical methods for welding the nanofibers involve thermal annealing, [6][7][8] chemical cross-linking, [9,10] and solvent or vapor treatment. [11][12][13] These methods have been applied to enhance the mechanical strength of nanofiber mats comprised of various polymers, including poly(e-caprolactone) (PCL), poly(lactic-co-glycolic acid), polyacrylonitrile,polysulfone,and ablend of poly(vinyl pyrrolidone) and In 2 O 3 precursor,b yr einforcing inter-fiber connection. [6,[11][12][13] In general, all these methods lack the feasibility and versatility for patterning (that is,w elding the nanofibers in as patially controlled manner) because all nanofibers in the mat will be welded, or, at least, affected.…”
mentioning
confidence: 99%
“…[11][12][13] These methods have been applied to enhance the mechanical strength of nanofiber mats comprised of various polymers, including poly(e-caprolactone) (PCL), poly(lactic-co-glycolic acid), polyacrylonitrile,polysulfone,and ablend of poly(vinyl pyrrolidone) and In 2 O 3 precursor,b yr einforcing inter-fiber connection. [6,[11][12][13] In general, all these methods lack the feasibility and versatility for patterning (that is,w elding the nanofibers in as patially controlled manner) because all nanofibers in the mat will be welded, or, at least, affected. When treated with asolvent in the liquid or vapor format, the nanofibers may also suffer from dimensional shrinkage owing to the relaxation of polymer chains.…”
mentioning
confidence: 99%
“…
challenge associated with these existing techniques is the inability to create nonwoven fabrics unless post deposition treatment is applied to obtain interconnected fiber junctions. [12][13][14][15] Recent progress in precision electrospinning techniques, such as near-field electrospinning (NFES), [16,17] electrohydrodynamic writing, [18] and lowvoltage electrospinning patterning, [19] have extended the fiber patterning capability, approaching that of a direct-writing fashion. Since these techniques rely on the close spineret-to-collector distance to obtain a stable jet, solvent evaporation may be incomplete depending on various parameters, including the target to collector distance.
…”
mentioning
confidence: 99%